Evaluation of The Success of Forest Reclamation on Coal Mining Land in The IUP Air Laya Mining Pt. Bukit Asam Tbk, Kab. Muara Enim, South Sumatra: Evaluasi Keberhasilan Reklamasi Hutan pada Lahan Tambang Batubara di IUP Tambang Air Laya PT. Bukut Asam Tbk, Kab. Muara Enim, Sumatera Selatan - Maharani, Jihan Putri; Kundarto, M. (Universitas Pembangunan Nasional Veteran Yogyakarta, 2024)
Coal mining activities can cause significant ecosystem changes. This needs to be remedied by reclamation. In reality, reclamation carried out in the field is not always successful, hence the need for monitoring This study integrates remote sensing technology in the form of aerial photo analysis and spatial mapping using the ArcGIS application, combined with biophysical assessments in the field. The purpose of this study is to quantitatively assess the success rate of post-mining land reclamation in the area of ​​the Air Laya Mining IUP of PT. Bukit Asam Tbk and to identify factors that support or hinder the reclamation process. This study uses the Minister of Forestry Regulation No. P.60 of 2009 with parameters of land management, erosion and sedimentation control, and revegetation. Data was collected using reference study, survey, sampling, scoring and analysis. The revegetation plants used are revegetation with the age of 1 years, 2 years and 5 year. Revegetation assessment was conducted by purposive sampling, based on planting year and ease of access using sample plots. The number of sample plots was determined as 5% of the total reclamation area. The number of sample plots observed was 6 plots with a size of 40 x 25 m. The results showed that reclaimed land with revegetation aged 5 and 2 years fell into the good and successful category with evaluation scores of 81 and 85. Whereas on reclaimed land with 1 year old revegetation is included in the medium category and is acceptable but must be improved again with an evaluation value of 75.5. Inhibiting factors for the reclamation process include poor integration of drainage channels, very acidic soil pH, and lack of local plants.